« En femme » à la gare Saint-Charles : la prostitution des Algériens à Marseille - Laurent Gaissad (L’Année du Maghreb)
The arrival in Marseilles of the first transvestites from Algeria in the 1980s upset the structure of local prostitution on the fringes of a neighbourhood where an internationally-known Maghreb commercial organization had settled. This contribution intends to break away from the spectacular dimension of exotic identities or the risks associated with AIDS, to return to the itineraries of transvestites, showing that they cannot be viewed as mere displacements in space, from one bank of the Mediterranean to another. They materialize primarily in the distance that separates the world of standards, revealing original biographies often marked by radical transitions from one situation to another in daily life, and from an ethics of secrecy associated with public disorder that may result from these itineraries in terms of “gender” and sexuality.